Child-Friendly Justice – Hungarian Perspective - Nagy, Adrienn (Child-Friendly Justice. The Participation and the Rights of the Child in Court Proceedings From a Central European Comparative Perspective, 2025)
Abstract:Hungary was the first of the Central and Eastern European countries to sign the Convention on the Rights of the Child (CRC) on 14 March 1990. This was promulgated by Act LXIV of 1991 and entered into force on 6 November 1991. The adoption of the CRC marked the beginning of the necessary harmonisation of legislation and the preparation of a law on the protection of children in accordance with the Convention. To ensure the effective exercise of the child’s right to participate guaranteed by Article 12 of the CRC, it was necessary to amend the rules of the Hungarian administrative, civil, and criminal procedure laws. The objective of this book chapter is to explore how children’s right to participate is enforced in Hungarian administrative, civil, and criminal proceedings and the related national practice. It is necessary to analyse the relevant sections of the Hungarian Fundamental Law, the rules of Act XXXI of 1997 on the Protection of Children and the Administration of Guardianship, the Code of Civil Procedure and Civil Code, and finally, the rules of Code of Criminal Procedure. In addition to the legal provisions, the main case law of the Hungarian courts is also presented. Keywords: procedural rights of children in Hungary, children’s right to participate in Hungarian administrative, civil and criminal proceedings, children’s right to express their views in Hungarian judicial proceedings, child who has sufficient understanding of Hungarian law